Analisis Persepsi dan Preferensi Mahasiswa Universitas Nurtanio Bandung terhadap Pelaksanaan Perkuliahan Pasca Pandemi - Rifka Agustianti; Deni Ramdani; Rahmi Mudia Alti; Yoana Nurul Asri (Departement of Mathematics Education, 2024)
The role of information and communication technology has become increasingly needed by society since the Covid-19 pandemic, one of which is in online lecture activities. With the decline in Covid-19 cases, there are differences of opinion among students about whether or not to carry out online learning like during a pandemic. This research aims to analyze and understand students' opinions about optimal learning systems in the post-pandemic period, with the hope that this can be used as material for consideration in understanding effective lecture methods for carrying out the lecture process after the pandemic. This research uses quantitative descriptive methods to explain numerical data obtained from students who participated in the research. Quantitative data collection was carried out through questionnaires to active students at Nurtanio University Bandung. Data analysis uses descriptive statistics to describe student opinions regarding student perceptions and preferences for online and offline lectures. Testing the validity and reliability of the instrument used was carried out using SPSS 25. From the test results, a valid and reliable instrument was obtained so that it could be analyzed further. From the results of the analysis, it can be concluded that after the pandemic, students' preference for lectures is offline, online lectures can be carried out as needed with a duration of less than 2-4 hours a day.